College Women's Leadership Self-Efficacy: An Examination Through the Framework of Emotionally Intelligent Leadership. Issue 3 (2nd September 2018) - Haber-Curran, Paige; Miguel, Rosanna; Shankman, Marcy Levy; Allen, Scott
Abstract : How women understand and practice leadership is a growing focus in research and in practice. This study was the first of its kind to examine different variables that drive college women's leadership self-efficacy. The researchers sought to identify which of the 19 capacities of emotionally intelligent leadership (EIL) are significant drivers of college women's leadership self-efficacy. Four EIL capacities emerged as significant: initiative, facilitating change, developing relationships, and managing conflict. The findings and discussion include specific strategies to support college women's leadership development and suggest further exploration of gender disparities in college student leadership development.